A new flavan glucoside from Glochidion eriocarpum. - Thư, Vũ Thị Kim; Kiệm, Phan Văn; Minh, Châu Văn; Yến, Phạm Hải; Cường, Nguyễn Xuân; Hương, Hoàng Thanh (Vietnam Journal of Chemistry, 2012)
From the aerial parts of Glochidion eriocarpum, a new flavan glucoside, 5,7,3',4'-tetra-O-methyl-ent-epicatechin 3-O-b-D-glucopyranoside (1), a known flavan, 5,7,3’,4’-tetra-O-methylepicatechin (2), and three known triterpenes, lupeol (3), 3-epi-lupeol (4), and glochidonol (5), were isolated by using combined chromatographic separations. Their structures were elucidated on the basis of spectroscopic data.